The Influence of Performing Arts Competitions on the Formation of Artistic and Pedagogical Space - Kamenets, Aleksandr Vladlenovich; Anufrieva, Natalia Ivanovna; Grushina, Elizaveta Evgenievna; Gribkova, Galina Ivanovna; Ershova, Olga Victorovna; Yushchenko, Natalia Sergeevna (Edelweiss Applied Science and Technology, 2021)
The article deals with the main pedagogical problems of performing arts competitions in the context of the humanistic paradigm of the forming artistic and pedagogical space. Different pedagogical situations determining the requirements for organizing and conducting contest programs are analyzed. Various pedagogical strategies of involving the younger generation in performance activities that ensure mass participation and provide children and adolescents with access to creative activities regardless of the level of their performing abilities are proposed. The article also pays special attention to the creation of a pedagogical environment that motivates children and adolescents to participate in contest performance; the organizational conditions of the competition that minimize the negative psychological effects on its participants are highlighted and further prospects for their improvement from the point of humanistic art pedagogy are outlined. The pedagogical problems considered in the article allow the authors to conclude on the need for greater use of the achievements of theater pedagogy in work with contestants, as well as for a thought-out differentiation of competition programs accounting for the composition of the participants and the nature of the pedagogical problems.